Antilipoxygenase and Anti-Inflammatory Activities of Streblus asper Leaf Extract on Xylene-Induced Ear Edema in Mice - Kanathip Singsai; Pimchanok Charoongchit; Waritsara Chaikaew; Nirut Boonma; Pitsinee Fhanjaksai; Karitta Chaisatan (Hindawi Limited, 2020)
Streblus asper (SA) belonging to the Moraceae family is well known as a folk medicinal plant in Asian countries. This study aimed to investigate the antilipoxygenase activity and the anti-inflammatory effects of the SA leaf extract. An in vitro antilipoxygenase study was performed using a lipoxygenase assay, and the oxidation of linoleic acid into 13-hydroperoxy linoleic acid (HPODE) was detected with a UV spectrophotometer at a wavelength of 234 nm. In the animal study, twenty-five male ICR mice were induced as ear edema by topical xylene, and the ear thickness of the mice was measured. The lipoxygenase assay results showed that the IC50 values of diclofenac sodium and SA were 0.0015 and 37.96 μg/mL, respectively. In the animal study, mice that received diclofenac sodium exhibited significantly reduced ear edema induced by xylene from 30 min onward, while mice that received 250 mg/kg and 500 mg/kg SA exhibited significantly reduced ear edema compared with the control group 45 min after induction with xylene. These results suggested that the SA leaf extract had anti-inflammatory activity. However, further studies are required to evaluate these effects and the additional potential of the plant that might be beneficial for the development of pharmaceutical products that prevent and treat inflammation.